Characteristics of Acute Pharyngitis at Dr. M. Djamil General Hospital, Padang, Indonesia - Sari, Puspa; Adelia (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Pharyngitis presents with a variety of symptoms, including sudden sore throat, fever, headache, lymphadenitis, and sometimes abdominal pain, nausea, fatigue, and/or rash. This study aimed to provide data on the basic characteristics of acute pharyngitis patients at Dr. M. DjamilGeneral Hospital, Padang, Indonesia. Methods: This study was a descriptive observational study. This study uses secondary data obtained from medical record data at the medical records installation of Dr. M. Djamil General Hospital, Padang, Indonesia. A total of 100 research subjects participated in this study, and the research subjects met the inclusion criteria. The inclusion criteria in this study were patients diagnosed with acute pharyngitis at Dr. M. Djamil General Hospital, Padang, Indonesia, for the period January – December 2022 and who have complete medical record data. Data analysis was carried out using SPSS version 25. Results: The majority of research subjects are in the age range of 0-14 years. The majority of research subjects are female. The majority of research subjects had clinical symptoms of sore throat and difficulty swallowing. The symptoms that arise in acute pharyngitis depend on the microorganisms that accompany it. Acute pharyngitis caused by bacteria is characterized by severe headache, fever or chills, malaise, painful swallowing, vomiting, and possibly coughing but rarely. Conclusion: The characteristics of pharyngitis patients at Dr. M. Djamil General Hospital, Padang, Indonesia, are aged 0-14 years with prominent clinical symptoms of sore throat and difficulty swallowing.